Radici senza dogmi. Vittorio Garatti, Roberto Gottardi, Ricardo Porro e l’esperienza delle Scuole Nazionali d’Arte a Cuba - Pietropaolo, Lorenzo (Studi e ricerche di storia dell'architettura, 2025)
This paper explores the biographical, cultural, and architectural paths that lead Italian ‘expatriates’ Vittorio Garatti and Roberto Gottardi, along with Cuban exile Ricardo Porro, to meet in Caracas and to reunite in Havana where they contributed to shape the internationalist dream of the Revolution through the creation of the Art Schools (1961-1965). Following this period, they each embarked on individual journeys, experiencing a diaspora of personal destinies, and they finally met again, thirty years later, in the ‘rediscovery’ of the Schools. Their experience exemplifies the interconnectedness and “crossbreeding” that makes Latin America — and with it the Caribbean Mediterranean, a meeting space of triangulations with Europe, Africa, and North America — an original laboratory of modernity. The paper aims to reflect on the legacy of the Schools and explore the potential insights it may offer for contemporary architectural culture.